2011
DOI: 10.3389/fnint.2011.00053
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Pathways Involved in Generating and Sensing Rhythmic Whisker Movements

Abstract: The rodent whisker system is widely used as a model system for investigating sensorimotor integration, neural mechanisms of complex cognitive tasks, neural development, and robotics. The whisker pathways to the barrel cortex have received considerable attention. However, many subcortical structures are paramount to the whisker system. They contribute to important processes, like filtering out salient features, integration with other senses, and adaptation of the whisker system to the general behavioral state o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
231
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(240 citation statements)
references
References 472 publications
(761 reference statements)
9
231
0
Order By: Relevance
“…In TDI, the barrelette connectivity map was seen in the coronal view in the ventro-lateral and interpolar regions as shown in cytochrome oxidase staining to demarcate the barrelettes in these regions (Li et al, 1994). Conversely, our results showed that the stereotypical barrelette connectivity map was not clearly detected using TDI in the oral part, consistent with current and previous histologic findings (Belford and Killackey, 1979;Bosman et al, 2011;Ma, 1991;Ma and Woolsey, 1984).…”
Section: Barrelettessupporting
confidence: 89%
“…In TDI, the barrelette connectivity map was seen in the coronal view in the ventro-lateral and interpolar regions as shown in cytochrome oxidase staining to demarcate the barrelettes in these regions (Li et al, 1994). Conversely, our results showed that the stereotypical barrelette connectivity map was not clearly detected using TDI in the oral part, consistent with current and previous histologic findings (Belford and Killackey, 1979;Bosman et al, 2011;Ma, 1991;Ma and Woolsey, 1984).…”
Section: Barrelettessupporting
confidence: 89%
“…Whiskers have been the subject of research in both rodents (Bosman et al, 2011) and marine mammals (Dehnhardt et al, 2001;Hanke et al, 2013), but studies in these animals have largely focused on separate aspects of whisker function.…”
Section: Introductionmentioning
confidence: 99%
“…The mystacial pad concerns the area directly under the nose, and comprises a highly uniform array of whiskers of varying length [2]. Whilst not all whiskers move, the mystacial pad of rodents is musculated, allowing the mammal hosts to 'whisker' -a motion of swaying the whiskers back and forth [3]. In rats, whisking happens at a dominant frequency of 8Hz [4].…”
Section: Introductionmentioning
confidence: 99%
“…In rats, whisking happens at a dominant frequency of 8Hz [4]. Whilst intrinsic and extrinsic muscles allow 'whisking' to occur, the whole mystacial pad is also changeable in shape [3]. As a tactile sensor array, this means the mystacial pad is highly adaptable with several degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%